The malaria in the second trimester of pregnancy (clinical case near miss) - A. S. Kovalchuk; A. N. Kutsheriavenko; D. S. Sudakov (Журнал инфектологии, 2024)
A clinical case of the course of malaria in a pregnant woman in the second trimester of pregnancy who returned from the Republic of Ghana is described. A multidisciplinary approach to the treatment of the disease made it possible to avoid the death of a woman. However, the extremely severe course of infection and the complications of this disease that have arisen have led to intrauterine fetal death.